Oral health challenges and management strategies for patients undergoing orthodontic treatment - Rapheal K. Falegbe; VE Adamu (Orapuh Journal)
Orthodontic treatment is a complex medical procedure that involves a series of steps aimed at achieving a desired outcome over an extended period, utilizing various types of appliances to correct malocclusion. This review seeks to explore common oral health issues faced by patients undergoing orthodontic treatment and to recommend effective strategies for addressing these problems. To gather relevant information, we conducted a comprehensive literature search across several databases, including PubMed/Medline, Google Scholar, JSTOR, Medscape, Elsevier, ResearchGate, Academia, Intechopen, and Sagepub, retrieving over 120 papers. The inclusion criteria were papers published in English between 2017 and 2021 within the review's subject area. From this pool, 50 papers were selected and thoroughly examined to provide the information presented in this article. The review is structured around orthodontic treatment concepts, types of appliances used to correct malocclusion, and the associated oral health conditions in patients, along with their management strategies. In conclusion, maintaining a high standard of oral hygiene is crucial for all patients undergoing orthodontic treatment. Patients should be educated on proper daily oral hygiene practices and encouraged to attend regular dental check-ups and prophylactic treatments.